ALLEVIATION OF MYCORRHIZA TO MAGNESIUM DEFICIENCY IN TRIFOLIATE ORANGE: CHANGES IN PHYSIOLOGICAL ACTIVITY - Zhang, Fei; Du, Peng; Song, Chang-Xu; Wu, Qiang-Sheng (Emirates Journal of Food and Agriculture, 2015)
Deficiency of magnesium (Mg) is quite common in citrus trees and often results in leaf chlorosis. In this study, five-leaf-old trifoliate orange (Poncirus trifoliata) seedlings were grown in sands and inoculated with an arbuscular mycorrhizal fungus (AMF), Funneliformis mosseae. After 8 days of transplanting, the seedlings were subjected to Mg-deficient (0.2 mM Mg2+) and Mg-sufficient (2 mM Mg2+) treatments for 92 days. Growth performance, chlorophyll concentration, soluble protein concentration, and antioxidant enzyme activities were determined. The results showed that root AMF colonization was significantly higher under Mg-deficiency than under Mg-sufficiency. AMF inoculation significantly increased leaf, stem, root, and total (leaf+ stem+root) biomass production and third-order lateral root number than non-AMF treatment under Mg-deficient and Mg-sufficient conditions. Compared with Mg-sufficiency, Mg-deficiency considerably reduced chlorophyll a and chlorophyll a+b concentration, whereas AMF inoculation significantly increased chlorophyll a and chlorophyll a+b concentration, representing the alleviation of leaf chlorosis by mycorrhization. The AMF seedlings presented significantly higher concentration of soluble protein concentration in leaf and root and activity of superoxide dismutase and catalase in root than the non-AMF seedlings exposed to Mg-deficient and Mg-sufficient, respectively. It concludes that AMF inoculation had positive effects on growth performance and physiological activities of trifoliate orange under Mg deficient condition, thus, possibly enhancing tolerance to Mg deficiency.